1979
DOI: 10.1080/03601237909372125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sub‐chronic low‐level dietary intake of chlordane on rats with cirrhosis of the liver.

Abstract: Male rats, 60 days old, were treated with chlordane during or after induction of liver cirrhosis with carbon tetrachloride to determine the effect of treatment with chlordane on the response of the rats to the disease. When liver cirrhosis was induced simultaneously with chlordane treatment the disease symptoms were aggravated; the lipid content of the tissue was lowered significantly, growth rate was significantly lower than controls and there was no apparent replacement of damaged liver tissue by liver growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

1979
1979
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
1
3
1
Order By: Relevance
“…The reverse has also been shown to occur (24). A high degree of polyploidy coupled with induction of the microsomal enzyme system in groups D and E (14) was in contrast with expected results. There was no stimulation of the microsomal system in group C (14).…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…The reverse has also been shown to occur (24). A high degree of polyploidy coupled with induction of the microsomal enzyme system in groups D and E (14) was in contrast with expected results. There was no stimulation of the microsomal system in group C (14).…”
Section: Discussioncontrasting
confidence: 85%
“…In group C, and by corollary group E, after 10 weeks of exposure to CCl, there was hypertrophy of the liver, while in group D there was no such growth (14). This would be in agreement with Takata (24) if argued that the administration of CCI, and chlordane simultaneously stimulated the liver to produce functional proteins to metabolize the toxicants, at the expense of regeneration.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The same study found an inverse correlation between ovary length and chlordane levels in female polar bears. The liver appears to be the primary target organ of chlordane toxicity in experimental studies [9][10][11][12]19,23,24,27,47]; other target organs include the testis [18], kidney [12], and possibly the brain [13,20]. Table 22.2 summarizes the studies that highlight the effects of chlordane.…”
Section: Mammalian Oral Toxicity: Othermentioning
confidence: 99%